Agroecology as a counter-narrative to food globalization: family gardens in their genesis and future - Vergara Monterroza, Marlon Julio (2025)
Family gardens constitute a central pillar in agroecology’s counter-narrative to food globalization. This article explores their genesis as historical spaces of biocultural resistance and their future role in building resilient and equitable food systems. We analyze how these gardens have been crucial for preserving agrobiodiversity and traditional ecological knowledge, challenging industrial homogenization and commodity dependence. Through documentaryreview, we examine their current role in food autonomy and the socio-ecological resilience of communities facing global crises. The study also highlights their potential for economic reconfiguration through alternative marketingcircuits and community self-management models. Results emphasize that family gardens serve as essential laboratories for innovation and adaptation in a global agroecological transition that redefines food production and consumption. In conclusion, these gardens represent a viable and necessary strategy for a more sustainable and equitable food future.